Anxiety and perceived social support as moderators of cognitive and emotional well-being in populations affected by COVID-19 - Zegarra-Valdivia, Jonathan; Chino-Vilca, Brenda; Pérez-Fernández, Leandro; Casimiro-Arana, Milagros; Arana-Nombera, Harold; Gallegos-Manayay, Viviana Nayelli; Oliva-Piscoya, María del Rosario; Alamo-Medina, Reyna; Abanto-Saldaña, Eduardo; Vásquez-Zuñe, Nobuko; Pérez, Lisseth Detquizan; Gutierrez-Flores, Diana; et al. (Frontiers in Public Health, 2025)
IntroductionThe COVID-19 pandemic has raised significant concerns about its long-term impact on cognitive and emotional functioning. This study explores the role of anxiety and social variables in shaping cognitive performance among individuals with a history of COVID-19 infection.MethodsThis retrospective cross-sectional study included 227 Peruvian adults, classified into control, acute phase, and hyperinflammatory phase groups based on COVID-19 symptomatology. Cognitive performance was assessed using the Addenbrooke’s Cognitive Examination (ACE), focusing on global cognition. Anxiety levels, social cognition, and perceived social support were also measured. Moderation analyses were conducted to explore whether anxiety moderated the relationship between social cognition and perceived support, and whether support moderated the relationship between age and cognition.ResultsIndividuals with a history of COVID-19, particularly those in the acute and hyperinflammatory phases, showed significantly lower ACE scores than controls. Anxiety moderated the relationship between social cognition and perceived social support, with stronger associations at higher anxiety levels. Additionally, perceived support moderated the effect of age on cognitive performance, especially in individuals with low to moderate support.DiscussionThese findings highlight the complex interplay between psychological and social factors in cognitive functioning following COVID-19. Understanding these relationships is crucial for developing integrated interventions that address cognitive and psychosocial recovery in affected populations.